2016
DOI: 10.1111/jch.12808
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Left Ventricular Mass and Hypertrophy by Cardiovascular Magnetic Resonance Imaging in Pediatric Hypertension

Abstract: Cardiovascular magnetic resonance (CMR) imaging in adults is considered the gold standard for assessment of left ventricular mass (LVM) and left ventricular hypertrophy (LVH). The authors aimed to evaluate agreement of LVM measurements and LVH determination between echocardiography (ECHO) and CMR imaging in children with hypertension (HTN) confirmed by 24‐hour ambulatory blood pressure monitoring (ABPM). The children (n=22) underwent contemporaneous ECHO, CMR imaging, and ABPM. Patients had a mean body mass in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
(47 reference statements)
0
6
0
Order By: Relevance
“…21 studies show that the accuracy of electrocardiographic indexes in the diagnosis of LVH is unsatisfactory [13]. The ECG shows an area under the ROC curve of 0.55 with 14.7% sensitivity and 96.7% specificity [14] and the echocardiography shows an area under the ROC curve of 0.62 with 90% sensitivity and 25% specificity [15]. In clinical practice, echocardiography is the imaging technique of choice [16].…”
Section: Introductionmentioning
confidence: 99%
“…21 studies show that the accuracy of electrocardiographic indexes in the diagnosis of LVH is unsatisfactory [13]. The ECG shows an area under the ROC curve of 0.55 with 14.7% sensitivity and 96.7% specificity [14] and the echocardiography shows an area under the ROC curve of 0.62 with 90% sensitivity and 25% specificity [15]. In clinical practice, echocardiography is the imaging technique of choice [16].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, CMR is used in the evaluation of congenital heart disease, ant its use has been recently reported in children and young adults on maintenance dialysis (17, 18), and renal transplant recipients (19). Our group has described the utility of CMR in overweight hypertensive children and reported reproducibility (20). However, CMR is not yet widely available, is more expensive than echocardiography (ECHO), has disadvantages such as claustrophobia and the need for sedation in small children, and the data on its utilization in general pediatric population with HTN are lacking.…”
Section: Detection Methodsmentioning
confidence: 99%
“…20 In addition, the acquisition and interpretation of images, even by clinically experienced sonographers, is a challenge. 21 Furthermore, sex, body mass, and race are common confounding factors that interfere with the accurate estimation of LV mass. 22 Data from several studies have shown that LV volume and LV mass are greater in men than in women.…”
Section: Common Limitations Of Echocardiographymentioning
confidence: 99%